Corporate secretary as a driver of ethical standards and sustainable corporate governance - Berdenov Zharas Galimzhanovich (Theoretical Hypotheses and Empirical Results, 2025)
The corporate secretary has become a key figure in advancing ethical standards and promoting sustainable corporate governance in today’s dynamic business environment. Acting as a bridge between the board of directors, management, shareholders, and other stakeholders, the corporate secretary ensures that governance processes are transparent, accountable, and aligned with best practices. This article explores the strategic role of the corporate secretary in embedding ethics into decision-making, fostering a culture of integrity, and supporting long-term sustainability goals. By examining global trends and practical examples, we highlight how corporate secretaries can serve as catalysts for building resilient, responsible, and future-oriented organizations.